2021
DOI: 10.51441/biomedica/5-500
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality: A New Learning Experience among Health Care Professionals

Abstract: <p><strong>Background and Objective:</strong> Augmented Reality (AR) is an effective tool for learning as well as marketing with multilateral interactive communication. It allows brands to give their customers unique experiences with the convenience of tapping into their mobile devices. This study was conducted to assess the perceptions of healthcare professionals (HCPs) to learn through AR and its effectiveness in HCPs&rsquo; engagement and learning experience.</p> <p>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…AR has been demonstrated to spark curiosity in various scenarios such as museum visits and scientific learning [134], with its use as a learning medium shown to increase children's curiosity [135]. The use of AR technology has been found to stimulate learning curiosity among healthcare professionals, indicating its potential to enhance professional development and knowledge acquisition [136]. In summary, the literature indicates that AR has the potential to stimulate curiosity across different domains including education, museums and professional development.…”
Section: Curiositymentioning
confidence: 99%
“…AR has been demonstrated to spark curiosity in various scenarios such as museum visits and scientific learning [134], with its use as a learning medium shown to increase children's curiosity [135]. The use of AR technology has been found to stimulate learning curiosity among healthcare professionals, indicating its potential to enhance professional development and knowledge acquisition [136]. In summary, the literature indicates that AR has the potential to stimulate curiosity across different domains including education, museums and professional development.…”
Section: Curiositymentioning
confidence: 99%
“…To date various fields of social life have been influenced by AR/VR technologies extending to entertainment, marketing and even the industrial processing fields. Jawaid et al 6 in their study concluded that AR is a useful tool to enhance user experience for learning as well as improves brand recall and can be used for marketing campaigns. AR/VR has also been extended to the field of medicine particularly surgically focused disciplines involving the minimally invasive approaches such as the endoscopic and laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%